THE MUCORMYCOSIS CRISIS: AN EPIDEMIC WITHIN A PANDEMIC - Aamir, Asma; Hanif , Faisal (Infectious Diseases Journal of Pakistan, 2023)
With the second wave of COVID-19 in the April of 2021, the deadly mucormycosis outbreak surfaced in South Asia. Mucormycosis infection is an uncommon yet perilous angio-invasive fungal infection with a fatality rate of 54% globally. Immunocompromised COVID-19 patients with underlying comorbidities like diabetes mellitus and who were on prolonged steroid medications were the most vulnerable to develop this infection. Regionally, a highly disproportionate increase in COVID-19 associated mucormycosis (CAM) was observed. While there has been vigorous attention on the pathological risk factors, little attention has been paid to the environmental factors specific to different regions which may explain the grotesque increase in CAM cases in some regions while ordinary increase in the other. Recognizing the interplay between the two factors will aid epidemiologists in understanding the spread of the disease and help prevent future epidemics. This review analyzes the current literature on CAM to update clinicians on circumstances that lead to outbreak. Keywords: Covid-19 Associated Mucormycosis, Mucormycosis, South Asia.